Pour une esthétique de l'émancipation: construire les lignées d'un art queer - Alfonsi, Isabelle; Fraisse, Geneviève; Abonnenc, Mathieu K. (Mathieu Kleyebe) (Culture, 2019)
"Loin de relire l'histoire de l'art en lui appliquant de façon anachronique le terme « queer », utilisé positivement dans les milieux militants depuis la fin des années 1980, Pour une esthétique de l'émancipation cherche à montrer comment l'écriture de l'Histoire de l'art a minoré l'importance des engagements politiques et affectifs des artistes et rendu inopérante la portée sociale de leurs œuvres. En imaginant des amitiés inédites entre des artistes du passé, Isabelle Alfonsi fait émerger une lignée féministe et queer pour l'art contemporain. Des pratiques artistiques du XXe siècle sont ainsi replacées dans le contexte du militantisme de défense des droits des homosexuel•le•s et de la formation d'une critique radicale féministe et anticapitaliste. Claude Cahun et Michel Journiac croisent l'histoire du minimalisme états-unien, vu à travers Lynda Benglis, Lucy Lippard ou Yvonne Rainer. Les guerres de représentation menées pendant la crise du sida sont lues au prisme des oeuvres de Felix Gonzalez-Torres, du concept de désidentification de José E. Muñoz et de l'activisme culturel du groupe Boy/Girl with Arms Akimbo, dans le San Francisco des années 1980."-- Résumé de l'éditeur.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; activisme; approches et analyses; artistes queers; arts; cours; discipline; har4600; histoire de l'art; histoire et politique; militance; premier cycle; périodes historiques; queer; thématiques; émancipation

Art & queer culture - Lord, Catherine; Meyer, Richard (Phaidon, 2019)
Spanning 125 years, Art and Queer Culture is the first major historical survey to consider the ways in which the codes and cultures of homosexuality have provided a creative resource for visual artists. Attempts to trouble the conventions of gender and sexuality, to highlight the performative aspects of identity and to oppose the tyranny of the normal are all woven into the historical fabric of homosexuality and its representation. From Oscar Wilde to Ryan Trecartin, from the molly houses of eighteenth-century London to the Harlem drag balls of the 1920s, the flamboyant refusal of social and sexual norms has fuelled the creation of queer art and life throughout the modern period. Although the book proceeds in a chronological fashion, it does not propose a progressive narrative in which homosexuals become increasingly adept at negotiating the circumstances of censorship and overcoming the terms of stigma and invisibility. The dialogue between art and queer culture does not move towards ever more affirmative images of equality and dignity. Rather than countering homophobia with 'positive' images of assimilation, many of the artists and photographers featured in this book draw upon, and even draw out, the deviant force of homosexuality. Art and Queer Culture includes not only pictures made and displayed under the rubric of fine art but also those intended for private, underground or otherwise restricted audiences. Scrapbooks, amateur artworks, cartoons, bar murals, anonymous photographs, activist posters, all appear in its pages, as do paintings, sculptures, art photographs and video installations. Writing queer culture into the history of art means redrawing the boundaries of what counts as art as well as what counts as history. It means searching for cracks in the partition that separates 'high' art from 'low' culture and in the divide between public achievement and private life
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes queers; arts; cours; discipline; europe; fem1000; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; thématiques; états-unis

Les amitiés radicales - Toffoli, Camille (Liberté, 2019)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; hétérosexisme; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; systèmes d'oppressions; thématiques; travail social; trs1205; états-unis